Taming the wild aborigines and racial knowledge in colonial Malaya - Manickam, Sandra Khor (Southeast Asia publications series., 2015)
A brilliant demonstration of how so-called scientific knowledge is framed by the political circumstances and popular beliefs of the time, this book investigates the racial categorization of 'aborigines' and the interaction between the emerging discipline of anthropology and the evolving colonial administration in Malaya